Fiber sizing agents, fiber bundles, molding materials, and molded products
The fiber sizing agent with a blocked polyurethane aqueous dispersion addresses fluidity and stability issues, enabling high-strength molded products by enhancing fiber bundling and compounding stability.
Patent Information
- Application Number
- JP2020192337
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-11-19
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2040-11-19
AI Technical Summary
Existing fiber sizing agents for carbon and glass fibers face issues with fluidity, supplyability, storage stability, compounding stability, and fiber bundling properties, leading to poor performance in producing high-strength molded products.
A fiber sizing agent containing a blocked polyurethane aqueous dispersion, composed of polyether polyol, aliphatic or alicyclic diisocyanate, a blocking agent, and a chain extender, is used to enhance fluidity and stability, with specific additives for improved adhesion and strength.
The proposed sizing agent improves the fluidity and storage stability of fiber bundles, resulting in high-strength molded products with enhanced compounding stability and fiber bundling properties.
Smart Images

Figure 0007608797000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a fiber sizing agent, a fiber bundle, a molding material, and a molded article. [Background technology]
[0002] Carbon fiber and glass fiber are used as reinforcing materials for matrix resins such as thermoplastic resins and thermosetting resins, and fiber-reinforced plastics obtained from glass fiber or carbon fiber and matrix resins are used as automobile and aircraft components that require high strength and excellent durability.
[0003] As the carbon fibers and glass fibers used in the reinforced plastics, from the viewpoint of imparting production processability, fiber materials bundled to about several thousand to several tens of thousands by a fiber bundling agent are often used, and various bundling agents have been proposed (for example, see Patent Document 1). This glass fiber bundling agent is a self-crosslinking dispersion based on a specific polyurethane, polyurethane-polyurea or polyurea containing a blocking agent, but the chopped strands obtained by cutting the fiber bundle obtained using this bundling agent have a large angle of repose, and there was a problem in the feedability from a feeder when kneading with a matrix resin. Therefore, there was a demand for a material that has excellent flowability and no feedability problems, can be used to manufacture a fiber bundle that can impart excellent strength to a molded product, and has excellent storage stability, compounding stability, and fiber bundling properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 4740460 Summary of the Invention [Problem to be solved by the invention]
[0005] The problem to be solved by the present invention is to provide a fiber sizing agent that has excellent flowability, can be used for producing fiber bundles that can impart excellent strength to molded articles, and has excellent storage stability, blending stability, and fiber bundling properties. [Means for solving the problem]
[0006] As a result of investigations aimed at solving the above-mentioned problems, the present inventors have found that the above-mentioned problems can be solved by using a fiber sizing agent containing a blocked polyurethane aqueous dispersion in which a specific blocked polyurethane is dispersed in water, and have thus completed the present invention.
[0007] That is, the present invention relates to a fiber sizing agent containing a blocked polyurethane water dispersion in which a blocked polyurethane is dispersed in water, characterized in that the blocked polyurethane is a reaction product of a polyether polyol (A), one or more diisocyanates (B) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a blocking agent (C), and a chain extender (D), and the polyether polyol (A) contains an alkylene oxide adduct of bisphenol A. Effect of the Invention
[0008] The fiber sizing agent of the present invention has excellent fluidity and can be used to produce fiber bundles that can impart excellent strength to molded products. In addition, since it has excellent storage stability, blending stability, and fiber bundling properties, it can be suitably used as a bundling agent for glass fibers and carbon fibers. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The fiber sizing agent of the present invention is a fiber sizing agent containing a blocked polyurethane aqueous dispersion in which a blocked polyurethane is dispersed in water, the blocked polyurethane being a reaction product of a polyether polyol (A), a diisocyanate (B), a blocking agent (C), and a chain extender (D), the polyether polyol (A) containing an alkylene oxide adduct of bisphenol A, and the diisocyanate (B) being an aliphatic diisocyanate and / or an alicyclic diisocyanate.
[0010] The blocked urethane will now be described. The blocked urethane is a reaction product of a polyether polyol (A), one or more diisocyanates (B) selected from the group consisting of aliphatic diisocyanates and alicyclic diisocyanates, a blocking agent (C), and a chain extender (D).
[0011] When the polyether polyol (A) contains an alkylene oxide adduct of bisphenol A, chopped strands with excellent fluidity can be obtained. In order to further improve the bundling ability, an adduct containing 3 to 20 moles of alkylene oxide is preferred, and an adduct containing 3 to 10 moles of ethylene oxide is more preferred.
[0012] The polyether polyol (A) other than the alkylene oxide adduct of bisphenol A preferably contains a polyol having a polyoxyethylene structure, and it is preferable to use polyethylene glycol because it improves the stability of the aminosilane blend. It is also preferable to contain polytetramethylene glycol because it prevents the strength of the molded product from decreasing after PCT (pressure cooker test). These polyether polyols (A) can be used alone or in combination of two or more kinds.
[0013] The content of the alkylene oxide adduct of bisphenol A in the polyether polyol (A) is preferably from 5 to 50 mass%, more preferably from 10 to 30 mass%, since this can reduce the angle of repose of the resulting chopped strands and impart excellent fluidity.
[0014] The content of the polyol having a polyoxyethylene structure in the polyether polyol (A) is preferably 10 to 50% by mass from the viewpoints of the water dispersibility and storage stability of the sizing agent.
[0015] By using the aliphatic diisocyanate and / or alicyclic diisocyanate as the isocyanate raw material for the blocked urethane, yellowing or coloring of a molded product using the obtained chopped strands can be suppressed.
[0016] Examples of the aliphatic diisocyanate include tetramethylene diisocyanate, hexamethylene diisocyanate, dodecamethylene diisocyanate, trimethylhexamethylene diisocyanate, lysine diisocyanate, etc. These aliphatic diisocyanates can be used alone or in combination of two or more kinds.
[0017] Examples of the alicyclic diisocyanate include 1,3-cyclopentylene diisocyanate, 1,3-cyclohexylene diisocyanate, 1,4-cyclohexylene diisocyanate, 1,3-di(isocyanatemethyl)cyclohexane, 1,4-di(isocyanatemethyl)cyclohexane, isophorone diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, 2,4'-dicyclohexylmethane diisocyanate, 2,2'-dicyclohexylmethane diisocyanate, 3,3'-dimethyl-4,4'-dicyclohexylmethane diisocyanate, etc. These alicyclic diisocyanates can be used alone or in combination of two or more kinds.
[0018] The blocking agent (C) may be any known blocking agent capable of reacting with an isocyanate group to protect the isocyanate group. Examples of the blocking agent include alcohol compounds such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butyl alcohol, isobutyl alcohol, and tert-butyl alcohol; phenol compounds such as phenol, methylphenol, chlorophenol, p-iso-butylphenol, p-tert-butylphenol, p-iso-amylphenol, p-octylphenol, and p-nonylphenol; active methylene compounds such as malonic acid dimethyl ester, malonic acid diethyl ester, acetylacetone, methyl acetoacetate, and ethyl acetoacetate; oxime compounds such as formaldoxime, acetaldoxime, acetone oxime, methyl ethyl ketone oxime, cyclohexanone oxime, acetophenone oxime, and benzophenone oxime; lactam compounds such as ε-caprolactam, δ-valerolactam, and γ-butyrolactam; N-substituted amide compounds such as N-methylacetamide and acetanilide; Examples of the amine compounds include imide compounds such as succinimide and phthalimide; imidazole compounds such as imidazole and 2-methylimidazole; pyrazole compounds such as pyrazole and 3,5-dimethylpyrazole, imine compounds such as ethyleneimine and polyethyleneimine; aliphatic secondary amine compounds having 2 to 15 carbon atoms such as dimethylamine, diisopropylamine, di-n-propylamine, diisobutylamine, etc.; alicyclic secondary amine compounds having 4 to 15 carbon atoms such as methylhexylamine and dicyclohexylamine, etc.; and aromatic secondary amine compounds such as aniline and diphenylamine. The blocked isocyanates stabilized with these blocking agents preferably have a decomposition temperature of 150° C. or higher, and desirably do not decompose at the drying temperature of ordinary sizing agents, about 130° C., but decompose at the temperature at which they are mixed with nylon resin or the like and molded to regenerate active isocyanate groups, and therefore, among these, lactam compounds having 2 to 6 carbon atoms such as ε-caprolactam, δ-valerolactam, and γ-butyrolactam are preferred, with ε-caprolactam being more preferred. These blocking agents can be used alone or in combination of two or more kinds.
[0019] Examples of the polyamine (D) include diamines such as ethylenediamine, 1,2-propanediamine, 1,6-hexamethylenediamine, piperazine, 2,5-dimethylpiperazine, isophoronediamine, 4,4'-dicyclohexylmethanediamine, 3,3'-dimethyl-4,4'-dicyclohexylmethanediamine, and 1,4-cyclohexanediamine; N-hydroxymethylaminoethylamine, N-hydroxyethylaminoethylamine, N-hydroxypropylaminopropylamine, N-ethylaminoethylamine, N- Examples of the polyamines include methylaminopropylamine, diethylenetriamine, dipropylenetriamine, triethylenetetramine, hydrazine, N,N'-dimethylhydrazine, 1,6-hexamethylenebishydrazine, succinic acid dihydrazide, adipic acid dihydrazide, glutaric acid dihydrazide, sebacic acid dihydrazide, isophthalic acid dihydrazide, β-semicarbazide propionic acid hydrazide, 3-semicarbazide propyl carbazate, semicarbazide-3-semicarbazide methyl-3,5,5-trimethylcyclohexane, etc. These polyamines can be used alone or in combination of two or more.
[0020] The blocked polyurethane is a reaction product having the polyether polyol (A), the diisocyanate (B), the blocking agent (C), and the polyamine (D) as essential raw materials, but other compounds can also be reacted.
[0021] The other compounds include polyols other than the polyether polyol (A) and polyoxyalkylene monoalkyl ethers, but it is preferable to use polyols having a carboxyl group and polyoxyethylene monoalkyl ethers because they further improve water dispersibility.
[0022] Examples of the polyol having a carboxyl group include hydroxy acids such as 2,2-dimethylolpropionic acid, 2,2-dimethylolbutanoic acid, 2,2-dimethylolbutyric acid, and 2,2-dimethylolvaleric acid; and reaction products of the polyol having a carboxyl group and the polycarboxylic acid, with 2,2-dimethylolpropionic acid being preferred. These may be used alone or in combination of two or more.
[0023] In terms of emulsion dispersibility and storage stability, the alkyl group of the polyoxyethylene monoalkyl ether is preferably a methyl group, an ethyl group, a propyl group, or a butyl group, and more preferably a methyl group. These may be used alone or in combination of two or more kinds.
[0024] The portion derived from the alkylene oxide adduct of bisphenol A in the blocked polyurethane is preferably 5 to 20% by mass, since this can reduce the angle of repose of the resulting chopped strands and impart excellent fluidity to the resulting chopped strands.
[0025] From the viewpoints of emulsification dispersibility and storage stability, the blocked polyurethane preferably contains a polyoxyethylene structure in an amount of 1 to 15% by mass, and more preferably 3 to 10% by mass.
[0026] The weight average molecular weight of the blocked polyurethane is preferably 5,000 to 20,000 from the viewpoints of reducing the bundling property of the fiber bundle and the angle of repose of chopped strands obtained from the fiber bundle.
[0027] The blocked polyurethane can be produced, for example, by subjecting polyether polyol (A), diisocyanate (B), blocking agent (C), polyamine (D), and other compounds, if necessary, to a urethane reaction by a conventionally known method in the absence of a solvent or in the presence of an organic solvent. Specifically, in consideration of safety, the reaction is preferably carried out at a reaction temperature of 50 to 120°C for 1 to 15 hours.
[0028] The polyamine (D) is preferably used in such a range that the equivalent ratio between the amino groups in the polyamine and the excess isocyanate groups is 1.9 or less (equivalent ratio), and more preferably in the range of 0.3 to 1.0 (equivalent ratio).
[0029] The urethanization reaction can be carried out without a catalyst, but a known catalyst may be used, for example, a tin compound such as stannous octoate, dibutyltin dilaurate, dibutyltin dimaleate, dibutyltin diphthalate, dibutyltin dimethoxide, dibutyltin diacetylacetate, or dibutyltin diversatate, a titanate compound such as tetrabutyl titanate, tetraisopropyl titanate, or triethanolamine titanate, or a tertiary amine compound, or a quaternary ammonium salt.
[0030] The blocked polyurethane water dispersion is a dispersion of the blocked polyurethane in water, but may contain an organic solvent other than water that is miscible with water. Examples of the organic solvent include alcohol compounds such as methanol, ethanol, and isopropanol; ketone compounds such as acetone and methyl ethyl ketone; polyalkylene glycol compounds such as ethylene glycol, diethylene glycol, and propylene glycol; alkyl ether compounds of polyalkylene glycol; and lactam compounds such as N-methyl-2-pyrrolidone. From the viewpoint of safety and environmental load, it is preferable that the organic solvent is not contained.
[0031] As a method for dispersing the blocked polyurethane in water, a known water dispersion method can be used. However, a method in which the carboxyl group introduced into the blocked polyurethane is neutralized with a basic compound and then water is added is preferred because this method provides excellent emulsion dispersion stability.
[0032] Examples of the basic compound include organic amines such as ammonia, triethylamine, morpholine, monoethanolamine, and diethylethanolamine; and metal hydroxides including sodium hydroxide, potassium hydroxide, and lithium hydroxide.
[0033] The equivalent ratio of the basic group of the basic compound to the carboxyl group in the blocked polyurethane (basic group / carboxyl group) is preferably 0.8 to 2.0 from the viewpoints of emulsion dispersion stability and storage stability.
[0034] The mass ratio of the solid content in the fiber sizing agent of the present invention is preferably in the range of 2 to 80 mass %, and more preferably in the range of 10 to 70 mass %, since this further improves storage stability and coating workability.
[0035] In addition, the fiber bundling agent of the present invention may be used in combination with additives such as a blocked isocyanate compound (E), a silane coupling agent, a curing catalyst, a lubricant, a filler, a thixotropic agent, a tackifier, a wax, a heat stabilizer, a light resistance stabilizer, a fluorescent whitening agent, a foaming agent, a pH adjuster, a leveling agent, a gelling inhibitor, a dispersion stabilizer, an antioxidant, a radical scavenger, a heat resistance imparting agent, an inorganic filler, an organic filler, a plasticizer, a reinforcing agent, a catalyst, an antibacterial agent, a mildew inhibitor, a rust inhibitor, a thermoplastic resin, a thermosetting resin, a pigment, a dye, an electrical conductivity imparting agent, an antistatic agent, a moisture permeability improving agent, a water repellent, an oil repellent, a hollow foam, a compound containing crystal water, a flame retardant, a water absorbent, a moisture absorbent, a deodorizer, a foam stabilizer, an antifoaming agent, an antifungal agent, an antiseptic, an anti-algae agent, a pigment dispersant, an antiblocking agent, and a hydrolysis inhibitor, if necessary.
[0036] Examples of the blocked isocyanate (E) include blocked isocyanates obtained by blocking organic diisocyanate compounds such as alicyclic diisocyanates such as isophorone diisocyanate, aliphatic diisocyanates such as hexamethylene diisocyanate and trimethylhexamethylene diisocyanate, and aromatic diisocyanates such as tolylene diisocyanate and 4,4-diphenylmethane diisocyanate, adducts of these compounds with polyhydric alcohols, low-molecular-weight hydroxyl-containing polyester resins, low-molecular-weight hydroxyl-containing alkyd resins, water, or the like, and polymers of the above-mentioned organic diisocyanate compounds (including isocyanurate-type polyisocyanate compounds and uretdione compounds), with a known and commonly used blocking agent such as an oxime compound, a phenol compound, an alcohol compound, or a diketone compound. Among these, the decomposition temperature of the blocked isocyanate stabilized with a blocking agent is preferably 150°C or higher, and since it does not decompose at the drying temperature of a normal sizing agent, about 130°C, but decomposes at the temperature at which it is mixed with nylon resin or the like and molded to regenerate active isocyanate groups, and further, in order to prevent a decrease in strength of the molded product after PCT treatment, it is preferable to use a polymer of the above-mentioned organic diisocyanate compounds (including isocyanurate-type polyisocyanate compounds and uretdione compounds) blocked with a lactam compound such as ε-caprolactam, δ-valerolactam, or γ-butyrolactam. These blocked isocyanates can be used alone or in combination of two or more kinds.
[0037] When the fiber sizing agent of the present invention is used as a sizing agent for glass fibers, it is preferable to use a silane coupling agent in combination in order to further improve the adhesive strength of the sizing agent to the glass fibers.
[0038] Examples of the silane coupling agent include γ-(2-aminoethyl)aminopropyltrimethoxysilane, γ-(2-hydroxyethyl)aminopropyltrimethoxysilane, γ-(2-aminoethyl)aminopropyltriethoxysilane, γ-(2-hydroxyethyl)aminopropyltriethoxysilane, γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-(2-hydroxyethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropylmethyldiethoxysilane, γ-(2-hydroxyethyl)aminopropylmethyldimethoxysilane,
[0043] Examples of the usable silane include ethyldimethoxysilane, γ-(2-hydroxyethyl)aminopropylmethyldiethoxysilane, or γ-(N,N-di-2-hydroxyethyl)aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, γ-aminopropyltriethoxysilane, γ-aminopropylmethyldimethoxysilane, γ-aminopropylmethyldiethoxysilane, or γ-(N-phenyl)aminopropyltrimethoxysilane, γ-mercaptopropyltrimethoxysilane, γ-mercaptophenyltrimethoxysilane, and the like.
[0039] The silane coupling agent is preferably used in an amount of 1 to 30 parts by mass relative to 100 parts by mass of the blocked polyurethane.
[0040] In addition, the fiber sizing agent of the present invention can also be used in combination with, for example, vinyl acetate, ethylene vinyl acetate, acrylic, epoxy, urethane, polyester, polyamide, and other emulsions; styrene-butadiene, acrylonitrile-butadiene, acrylic-butadiene, and other latexes; and water-soluble resins such as poval and cellulose.
[0041] The fiber sizing agent of the present invention can be used for bundling a plurality of fibers or for surface treatment, for example, for the purpose of preventing breakage and fluffing of glass fibers, carbon fibers, etc.
[0042] Examples of fiber materials that can be treated using the fiber sizing agent of the present invention include glass fiber, carbon fiber, silicon carbide fiber, pulp, hemp, cotton, nylon, polyester, acrylic, polyurethane, polyimide, and polyamide fibers made of aramids such as Kevlar and Nomex, etc. Among these, glass fiber and carbon fiber are preferably used because of their high strength.
[0043] Examples of glass fibers that can be treated with the fiber bundling agent include those obtained from raw materials such as alkali-containing glass, low-alkali glass, and non-alkali glass. In particular, it is preferable to use non-alkali glass (E glass), which is less susceptible to deterioration over time and has stable mechanical properties.
[0044] In addition, the carbon fibers that can be treated with the fiber sizing agent may generally be polyacrylonitrile-based, pitch-based, etc. Among them, it is preferable to use polyacrylonitrile-based carbon fibers as the carbon fibers from the viewpoint of imparting excellent strength.
[0045] From the viewpoint of imparting even greater strength and the like, the carbon fibers to be used preferably have a single fiber diameter of 0.5 to 20 μm, and more preferably 2 to 15 μm.
[0046] The carbon fibers may be, for example, twisted, spun, spun or nonwoven.Furthermore, the carbon fibers may be, for example, filaments, yarns, rovings, strands, chopped strands, felts, needle punches, cloths, roving cloths, milled fibers, etc.
[0047] Examples of a method for bundling the glass fibers or carbon fibers using the fiber sizing agent of the present invention and forming a coating on the surface of the glass fiber bundle or carbon fiber bundle include a method in which the fiber sizing agent is uniformly applied to the fiber surface by a kiss coater method, a roller method, a dipping method, a spray method, a brush method, or other known method. When the fiber sizing agent contains an aqueous medium or an organic solvent as a solvent, it is preferable to heat and dry the applied fiber using a heated roller, hot air, a hot plate, or the like.
[0048] The amount of the coating formed on the surface of the fiber material is preferably 0.1 to 5 mass %, and more preferably 0.3 to 1.5 mass %, based on the total mass of the bundled and surface-treated fiber bundle.
[0049] The bundled and surface-treated fiber material obtained by the above method, particularly glass fiber or carbon fiber, can be used as a molding material for producing high-strength molded products by combining it with a matrix resin (F) described below, etc.
[0050] In particular, when a fiber material that has been surface-treated with the fiber sizing agent of the present invention is used in combination with a matrix resin (F) to form a molded product, etc., the adhesion at the interface between the fiber and the matrix resin (F) can be significantly improved, making it possible to improve the strength of the molded product.
[0051] The matrix resin (F) may be, for example, a thermosetting resin (F1) or a thermoplastic resin (F2). The thermosetting resin (F1) may be, for example, a phenol resin, a polyimide resin, a bismaleimide resin, an unsaturated polyester resin, an epoxy resin, a vinyl ester resin, or the like. The thermoplastic resin (F2) may be, for example, a saturated polyester resin such as polyethylene terephthalate or polybutylene terephthalate, a polyamide resin such as polypropylene, polystyrene, polycarbonate, polyphenylene sulfide, polyphenylene oxide, 6-nylon or 6,6-nylon, an acrylonitrile-styrene copolymer, an acrylonitrile-butadiene-styrene copolymer, polyacetal, polyetherimide, or polyether ether ketone.
[0052] In order to obtain a molded product having high strength, it is more preferable to use the fibers bundled using the fiber sizing agent of the present invention in combination with a matrix resin such as an epoxy resin, an unsaturated polyester resin, a polyamide resin such as 6-nylon or 6,6-nylon, polyphenylene sulfide, polybutylene terephthalate, polycarbonate, or polyether ether ketone.
[0053] Examples of the molding material containing the surface-treated fiber material, the matrix resin (F), and, if necessary, a polymerizable monomer, etc., include prepreg and sheet molding compound (SMC).
[0054] The prepreg can be produced, for example, by applying the matrix resin (F1) onto a release paper, placing a surface-treated fiber material on the applied surface, and, if necessary, pressing and impregnating the fiber material using a roller or the like.
[0055] When producing the prepreg, it is preferable to use, as the matrix resin (F1), an epoxy resin such as a bisphenol A type epoxy resin, a glycidylamine type epoxy resin such as tetraglycidylaminodiphenylmethane, or a novolac type epoxy resin.
[0056] The sheet molding compound can be produced, for example, by thoroughly impregnating the surface-treated fiber material with a mixture of the matrix resin (F1) and a polymerizable unsaturated monomer such as styrene, and processing the material into a sheet. When producing the sheet molding compound, it is preferable to use an unsaturated polyester resin or a vinyl ester resin as the matrix resin (D1).
[0057] The curing of the molding material proceeds, for example, by radical polymerization under pressure or normal pressure, heating or light irradiation. In such cases, a known heat curing agent or light curing agent can be used in combination.
[0058] The molding material may be, for example, a material obtained by kneading the thermoplastic resin (F2) and the surface-treated fiber material under heating, etc. Such a molding material may be used for secondary processing, for example, by injection molding.
[0059] Moreover, a prepreg made of the thermoplastic resin (F2) can be produced, for example, by placing a surface-treated fiber material in the form of a sheet and impregnating it with molten thermoplastic resin (F2).
[0060] The prepreg made of the thermoplastic resin (F2) can be used for secondary processing, for example by laminating one or more sheets and then heating and molding under pressure or normal pressure.
[0061] Molded articles obtained using the molding material have high strength and can be used, for example, as automobile parts, aircraft parts, industrial parts, etc. EXAMPLES
[0062] The present invention will now be described in more detail with reference to the following examples. The average molecular weight was measured under the following GPC measurement conditions.
[0063] [GPC measurement conditions] Measurement equipment: High-speed GPC equipment (Tosoh Corporation "HLC-8220GPC") Column: The following columns manufactured by Tosoh Corporation were used, connected in series. "TSKgel G5000" (7.8mm I.D. x 30cm) x 1 "TSKgel G4000" (7.8mm I.D. x 30cm) x 1 "TSKgel G3000" (7.8mm I.D. x 30cm) x 1 "TSKgel G2000" (7.8mmI.D. x 30cm) x 1 Detector: RI (differential refractometer) Column temperature: 40℃ Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Injection volume: 100 μL (sample concentration 4 mg / mL in tetrahydrofuran solution) Standard sample: A calibration curve was prepared using the following monodisperse polystyrene.
[0064] (monodisperse polystyrene) "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation
[0065] (Synthesis Example 1: Synthesis of Blocked Isocyanate (E-1)) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 1000 parts by mass of isocyanurate of hexamethylene diisocyanate ("Coronate HX" manufactured by Tosoh Corporation, NCO equivalent 199.2 g / equivalent), 575.0 parts by mass of ε-caprolactam (manufactured by Kanto Chemical Co., Ltd.; hereinafter, abbreviated as "blocking agent (C-1)"). was added and uniformly melted at 80 ° C., and then reacted until disappearance of the isocyanate group in the reaction solution was confirmed by infrared absorption spectrum at 80 ° C. Then, 1050 parts by mass of methyl ethyl ketone was added and uniformly dissolved to obtain a blocked isocyanate (E-1) with a solid content of 60% by mass.
[0066] (Example 1: Production of fiber sizing agent (1)) Into a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 350 parts by mass of polytetramethylene glycol (hydroxyl value 110.2 KOHmg / g, manufactured by Mitsubishi Chemical Corporation; hereinafter abbreviated as "polyether polyol (A-2)"), 68 parts by mass of an ethylene oxide 7.5 mole adduct of bisphenol A ("BA-4JU", manufactured by Nippon Nyukazai Co., Ltd.; hereinafter abbreviated as "polyether polyol (A-1)"), 28 parts by mass of polyethylene glycol (molecular weight 1000, manufactured by NOF Corporation; hereinafter abbreviated as "polyether polyol (A-3)"), 17 parts by mass of trimethylolpropane (manufactured by Kanto Chemical Co., Ltd.), dimethyl ether (A-4) (manufactured by Nippon Nyukazai Co., Ltd.), and dimethyl ether (A-4) (manufactured by Nippon Nyukazai Co., Ltd.). 22 parts by mass of tyrolpropionic acid (manufactured by Perstop Co., Ltd.), 22 parts by mass of polyoxyethylene monomethyl ether (ethylene oxide addition mole number 46, manufactured by NOF Corporation), and 400 parts by mass of methyl ethyl ketone were added and uniformly dissolved, and then 320 parts by mass of dicyclohexylmethane 4,4'-diisocyanate (manufactured by Covestro Co., Ltd., "Dismodul W"; hereinafter abbreviated as "diisocyanate (B-1)") and 90 parts by mass of hexamethylene diisocyanate (manufactured by Covestro Co., Ltd., "Dismodul H"; hereinafter abbreviated as "diisocyanate (B-2)") were added and reacted at 80°C until the theoretical NCO value was obtained. Next, 98 parts by mass of ε-caprolactam (manufactured by Kanto Chemical Co., Ltd.; hereinafter abbreviated as "blocking agent (C-1)") were added to the urethane prepolymer, and further reacted at 80°C until the theoretical NCO value was obtained. Thereafter, an aqueous solution in which 60 parts by mass of isophorone diamine (manufactured by Covestro, hereinafter abbreviated as "chain extender (D-1)") and 19 parts by mass of triethylamine (manufactured by Kanto Chemical Co., Ltd.) were uniformly dissolved in 3000 parts by mass of ion-exchanged water was added dropwise over 30 minutes. Thereafter, the mixture was held at 40°C, and the disappearance of the isocyanate group in the reaction solution was confirmed by infrared absorption spectroscopy. Thereafter, this aqueous dispersion was concentrated by distillation under reduced pressure to obtain a fiber sizing agent (1) consisting of a blocked polyurethane aqueous dispersion with a solid content of 35% by mass. The weight-average molecular weight of the blocked polyurethane was 11,220.
[0067] (Example 2: Production of fiber sizing agent (1)) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 350 parts by mass of polyether polyol (A-2), 68 parts by mass of polyether polyol (A-1), 28 parts by mass of polyether polyol (A-3), 18 parts by mass of dimethylol propionic acid (manufactured by Perstop Co., Ltd.), 18 parts by mass of polyoxyethylene monomethyl ether (ethylene oxide addition mole number 46, manufactured by NOF Corporation), and 400 parts by mass of methyl ethyl ketone were added and uniformly dissolved, and then 250 parts by mass of diisocyanate (B-1) and 75 parts by mass of diisocyanate (B-2) were added and reacted at 80 ° C. until a theoretical NCO value was obtained. Next, 100 parts by mass of blocking agent (C-1), isophorone diisocyanate-based isocyanurate (Evonik "VESTNAT 65 parts by mass of T1890 / 100 and NCO equivalent of 245.7 g / equivalent were added to the urethane prepolymer and further reacted at 80°C until the theoretical NCO content was obtained. Then, 159.2 parts by mass of blocked isocyanate (E-1) were added and uniformly dissolved and mixed. Then, an aqueous solution in which 45 parts by mass of chain extender (D-1) and 17 parts by mass of triethylamine (Kanto Chemical Co., Ltd.) were uniformly dissolved in 3000 parts by mass of ion-exchanged water was dropped and dispersed over 30 minutes. Then, the mixture was held at 40°C, and the disappearance of the isocyanate group in the reaction solution was confirmed by infrared absorption spectroscopy. Then, this aqueous dispersion was concentrated by distillation under reduced pressure to obtain a fiber sizing agent (2) consisting of an aqueous dispersion of blocked polyurethane with a solid content of 35% by mass. The weight-average molecular weight of the blocked polyurethane was 11,000.
[0068] (Example 3: Production of fiber sizing agent (3)) Into a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 350 parts by mass of polyether polyol (A-2), 68 parts by mass of polyether polyol (A-1), 28 parts by mass of polyethylene glycol (molecular weight 2000, manufactured by NOF Corporation; hereinafter abbreviated as "polyether polyol (A-4)"), 16 parts by mass of trimethylolpropane (manufactured by Kanto Chemical Co., Ltd.), 22 parts by mass of dimethylolpropionic acid (manufactured by Perstop Co., Ltd.), 22 parts by mass of polyoxyethylene monomethyl ether (ethylene oxide addition mole number 46, manufactured by NOF Corporation), and 400 parts by mass of methyl ethyl ketone were added and dissolved uniformly, and then isophorone diisocyanate ("VESTNAT" manufactured by Evonik) was added. 270 parts by mass of IPDI (hereinafter abbreviated as "diisocyanate (B-3)") and 90 parts by mass of diisocyanate (B-2) were added and reacted at 80 ° C. until the theoretical NCO value was obtained. Next, 98 parts by mass of blocking agent (C-1) was added to the urethane prepolymer and further reacted at 80 ° C. until the theoretical NCO value was obtained. Then, an aqueous solution in which 35 parts by mass of piperazine (manufactured by Tosoh Corporation; hereinafter abbreviated as "chain extender (D-2)") and 19 parts by mass of triethylamine (manufactured by Kanto Chemical Co., Ltd.) were uniformly dissolved in 3000 parts by mass of ion-exchanged water was dropped and dispersed over 30 minutes. Then, the mixture was held at 40 ° C., and the disappearance of the isocyanate group in the reaction solution was confirmed by infrared absorption spectroscopy. Then, this aqueous dispersion was concentrated by distillation under reduced pressure to obtain a fiber sizing agent (3) consisting of a blocked polyurethane aqueous dispersion with a solid content of 35% by mass. The weight average molecular weight of the blocked polyurethane was 10,200.
[0069] (Example 4: Production of fiber sizing agent (4)) Into a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 350 parts by mass of polyether polyol (A-4), 68 parts by mass of polyether polyol (A-1), 30 parts by mass of polyether polyol (A-2), 20 parts by mass of dimethylolpropionic acid (manufactured by Perstop Co., Ltd.), 20 parts by mass of polyoxyethylene monomethyl ether (ethylene oxide addition mole number 46, manufactured by NOF Corporation), and 400 parts by mass of methyl ethyl ketone were added and uniformly dissolved, and then 220 parts by mass of diisocyanate (B-3) and 70 parts by mass of diisocyanate (B-2) were added and reacted at 80° C. until the theoretical NCO value was obtained. Next, 100 parts by mass of blocking agent (C-1) and 65 parts by mass of isophorone diisocyanate-based isocyanurate (Evonik "VESTNAT T1890 / 100, NCO equivalent 245.7 g / equivalent") were added to the urethane prepolymer, and the mixture was further reacted at 80°C until the theoretical NCO content was obtained. Thereafter, 135.0 parts by mass of blocked isocyanate of IPDI ε-caprolactam (Evonik Japan Ltd., VESTAGON B-1530 (hereinafter referred to as blocked isocyanate E-2)) was added and uniformly dissolved and mixed. Then, an aqueous solution in which 30 parts by mass of a chain extender (D-2) and 15 parts by mass of triethylamine (manufactured by Kanto Chemical Co., Ltd.) were uniformly dissolved in 3000 parts by mass of ion-exchanged water was dropped and dispersed over 30 minutes. Then, the reaction solution was held at 40°C, and the disappearance of the isocyanate group in the reaction solution was confirmed by infrared absorption spectroscopy. Then, this aqueous dispersion was concentrated by distillation under reduced pressure to obtain a fiber sizing agent (4) consisting of an aqueous dispersion of blocked polyurethane with a solid content of 35% by mass. The weight-average molecular weight of the blocked polyurethane was 10,800.
[0070] (Example 5: Production of fiber sizing agent (5)) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 350 parts by mass of polyether polyol (A-2), 75 parts by mass of polyether polyol (A-1), 64 parts by mass of polyether polyol (A-4), 17 parts by mass of trimethylolpropane (Kanto Chemical Co., Ltd.), 22 parts by mass of dimethylolpropionic acid (Perstop Co., Ltd.), 22 parts by mass of polyoxyethylene monomethyl ether (ethylene oxide addition mole number 46, NOF Corporation), and 450 parts by mass of methyl ethyl ketone were added and uniformly dissolved, and then 340 parts by mass of diisocyanate (B-1) and 95 parts by mass of diisocyanate (B-2) were added and reacted at 80 ° C. until the theoretical NCO value was obtained. Next, 110 parts by mass of blocking agent (C-1) was added to the urethane prepolymer, and further reacted at 80 ° C. until the theoretical NCO content was obtained. Then, an aqueous solution in which 70 parts by mass of a chain extender (D-1) and 21 parts by mass of triethylamine (manufactured by Kanto Chemical Co., Ltd.) were uniformly dissolved in 3500 parts by mass of ion-exchanged water was dropped and dispersed over 30 minutes. Then, the mixture was held at 40°C, and the disappearance of the isocyanate group in the reaction solution was confirmed by infrared absorption spectroscopy. Then, this aqueous dispersion was concentrated by distillation under reduced pressure to obtain a fiber sizing agent (5) consisting of a blocked polyurethane aqueous dispersion with a solid content of 35% by mass. The weight-average molecular weight of the blocked polyurethane was 13,000.
[0071] (Example 6: Production of fiber sizing agent (6)) In a four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 350 parts by mass of polyether polyol (A-2), 70 parts by mass of polyether polyol (A-1), 40 parts by mass of polyethylene glycol (molecular weight 4000, manufactured by NOF Corporation; hereinafter, abbreviated as "polyether polyol (A-5)"), 16 parts by mass of trimethylolpropane (manufactured by Kanto Chemical Co., Ltd.), 22 parts by mass of dimethylolpropionic acid (manufactured by Perstop Co., Ltd.), 22 parts by mass of polyoxyethylene monomethyl ether (ethylene oxide addition mole number 46, manufactured by NOF Corporation), and 480 parts by mass of methyl ethyl ketone were added and uniformly dissolved, and then 320 parts by mass of diisocyanate (B-1) and 90 parts by mass of diisocyanate (B-2) were added and reacted at 80 ° C. until the theoretical NCO value was obtained. Next, 100 parts by mass of blocking agent (C-1) was added to the urethane prepolymer, and the reaction was continued at 80°C until the theoretical NCO content was obtained. Then, an aqueous solution in which 68 parts by mass of chain extender (D-1) and 20 parts by mass of triethylamine (manufactured by Kanto Chemical Co., Ltd.) were uniformly dissolved in 3500 parts by mass of ion-exchanged water was dropped and dispersed over 30 minutes. Then, the mixture was held at 40°C, and the disappearance of the isocyanate group in the reaction solution was confirmed by infrared absorption spectroscopy. Then, this aqueous dispersion was concentrated by distillation under reduced pressure to obtain a fiber sizing agent (6) consisting of a blocked polyurethane aqueous dispersion with a solid content of 35% by mass. The weight-average molecular weight of the blocked polyurethane was 13,000.
[0072] (Comparative Example 1: Production of fiber sizing agent (R1)) In a 10 L four-neck flask equipped with a thermometer, a stirrer, a reflux condenser, and a dropping device, 1170 parts by mass of polypropylene glycol (AGC Corporation's "Exenol 2020", hydroxyl value 112.2 KOHm / g), 135 parts by mass of polyether (Kobestro's "Polyether LB25", a monofunctional polyether based on ethylene oxide / propylene oxide), and 122.4 parts by mass of ethoxylated trimethylolpropane (Nippon Nyukazai Co., Ltd.'s "TMP-30", molecular weight 270, EO addition mole number 3.1) were placed in a 6 L reactor equipped with a stirrer, a cooling device, and a heating device, and homogenized at 60 ° C., and then reacted with 759 parts by mass of isophorone diisocyanate (Kobestro) until the theoretical NCO value was obtained. Next, 94.8 parts by weight of ε-caprolactam (Kanto Chemical Co., Ltd.) was added to the NCO-functional polyurethane prepolymer and stirred at 80 ° C until the theoretical NCO content was obtained, the mixture was diluted with 1500 parts by weight of acetone and reacted with 23.5 parts by weight of hydrazine and 125.3 parts by weight of a 25% aqueous solution of the reaction product of 1 mole of acrylic acid and 1 mole of isophorone diamine until no NCO groups were detected by infrared spectroscopy. After adding 24 parts by weight of Irganox 245 (Ciba-Geigy), 44 parts by weight of 4,4'-methylene-bis-cyclohexaneamine and 6 parts by weight of triethylamine were dispersed in 3000 parts by weight of water. After distilling off the acetone, a self-crosslinking fiber sizing agent (R1) was obtained, which has a solid content of 43% and contains blocked isocyanate groups and reactive diamines.
[0073] [Evaluation of storage stability] The fiber sizing agent obtained above was allowed to stand at 40° C. for 30 days, and the occurrence of precipitation and solidification of the liquid was observed to evaluate storage stability. ○: No change △: A small amount of precipitation occurs ×: A large amount of precipitate was generated or solidification occurred.
[0074] [Evaluation of aminosilane compounding stability] To 100 parts by mass of the solid content of the fiber bundling agent obtained above, 10 parts by mass of γ-aminopropyltriethoxysilane was added, and then the water-diluted solution prepared so that the non-volatile content was 20% by mass was left to stand at 40°C for 3 days, and the occurrence of any precipitate or solidification of the liquid was observed to evaluate the stability of the aminosilane blend. ◎: No change 〇: A small amount of precipitation occurs △: A little more sediment is generated ×: A large amount of precipitate was generated or solidification occurred.
[0075] [Chopped strand production] A glass fiber sizing agent was prepared by mixing 8.8 parts by mass (3 parts by mass as solid content) of the fiber sizing agent obtained above, 0.3 parts by mass of γ-aminopropyltriethoxysilane, and 90.9 parts by mass of ion-exchanged water. This glass fiber sizing agent was uniformly applied to the surface of glass fibers with a diameter of 13 μm at 1% by mass relative to the fiber mass, and the fibers were bundled, then cut to a length of 3 mm and dried to prepare chopped strands.
[0076] [Evaluation of convergence] 50 g of the chopped strands obtained above and 100 g of polyamide 66 (nylon) resin were placed in a 1 L tumbler and mixed for 10 minutes. The generated fluff was then collected and its mass was measured and evaluated according to the following criteria. ○: Less than 0.15g △: 0.15g or more and less than 1.5g ×: 1.5g or more
[0077] [Evaluation of fluidity (angle of repose)] Using 50 g of the chopped strands obtained above, the angle of repose was measured using a powder funnel with a nozzle of 14 mm inner diameter in accordance with the provisions of JIS R 9301-2-2, and the fluidity was evaluated according to the following criteria. The distance from the tip of the funnel's stem to the base was set to 100 mm. The smaller the angle of repose, the better the slip and the better the fluidity. ◎: Less than 20° ○: 20° or more and less than 30° △: 30° to less than 50° ×: 50° or more
[0078] [Production of molded products] A mixture consisting of 30% by mass of the chopped strands obtained above and 70% by mass of polyamide 66 (nylon 66) resin was heated at 270°C and extruded into pellets containing glass fiber reinforcement, and then the pellets were injection molded to produce FRTP molded products.
[0079] [Evaluation of tensile strength] The tensile strength of the FRTP molded product obtained above was measured in accordance with ASTM D638. The FRTP molded product obtained above was also subjected to a PCT (pressure cooker test) for 24 hours at 135°C, after which the tensile strength of the sample was similarly measured, and the tensile strength of the molded product was evaluated according to the following criteria. Dumbbell-shaped test pieces (Type I) were used as test pieces. ◎: 100MPa or more ○: 90MPa or more and less than 100MPa △: 70MPa or more and less than 90MPa ×: 70MPa or less
[0080] The evaluation results of Examples 1 to 6 and Comparative Example 1 are shown in Table 1.
[0081] [Table 1]
[0082] It was confirmed that Examples 1 to 6, which are fiber sizing agents of the present invention, are excellent in storage stability, blending stability, and sizing property, and can give fiber bundles with excellent flowability and molded products with excellent tensile strength.
[0083] On the other hand, Comparative Example 1 is an example of a fiber sizing agent using a blocked polyurethane water dispersion that does not satisfy the requirements of the present invention, and it was confirmed that the fluidity of the obtained fiber bundle was poor.
Claims
1. A fiber sizing agent containing a blocked polyurethane water dispersion in which a blocked polyurethane is dispersed in water and a blocked isocyanate (E), characterized in that the blocked polyurethane is a reaction product of a polyether polyol (A), a diisocyanate (B), a blocking agent (C), and a polyamine (D), the polyether polyol (A) contains an alkylene oxide adduct of bisphenol A, and the diisocyanate (B) is an aliphatic diisocyanate and / or an alicyclic diisocyanate.
2. 2. The fiber sizing agent according to claim 1, wherein the portion derived from the alkylene oxide adduct of bisphenol A in the blocked polyurethane is 5 to 20% by mass.
3. 3. The fiber sizing agent according to claim 1, wherein the blocking agent (C) is a lactam compound.
4. 4. The fiber sizing agent according to claim 1, wherein the polyether polyol (A) contains polyethylene glycol.
5. A fiber bundle characterized by being bundled with the fiber sizing agent according to any one of claims 1 to 4.
6. A molding material comprising the fiber bundle according to claim 5 and a matrix resin.
7. A molded article which is a cured product of the molding material according to claim 6.
Citation Information
Patent Citations
Size for warp yarn of synthetic fiber and its production
JP1996246355A
Aqueous resin composition
JP2002088229A
Mixture for reinforcing resin, fiber reinforced resin mixture, fiber reinforced resin and manufacturing method therefor
JP2017019889A
Polyurethane resin composition aqueous dispersion and method for producing the same
JP2018053245A
Self-crosslinking polyurethanes, polyurethane-polyureas, or polyurea dispersions for sizing agents
JP4740460B2